Analysis of tourists’ perceptions of the management of the Lubuk Pakam Fruit Garden Agrotourism destination in Deli Serdang Regency - Via Marlina; Dewi Shinta Wulandari Lubis (Universitas Nusa Cendana, 2026)
Public agritourism destinations play an important role in promoting environmental education, community engagement, and sustainable tourism development. However, maintaining service quality and destination sustainability remains a challenge, particularly for sites operating under non-profit and free-entry models. This study investigates tourists’ perceptions of destination management at Lubuk Pakam Fruit Park, Indonesia, through the lens of the 5A tourism attributes (attractions, accessibility, amenities, available packages, and ancillary services), identifies the cognitive factors shaping these perceptions, and proposes strategies for sustainable destination management. A descriptive qualitative approach was employed using passive participatory observation, in-depth interviews with 15 purposively selected informants, and secondary data analysis of Google Maps reviews and documentary evidence. Data credibility was ensured through source and technique triangulation, while analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings reveal an ambivalent pattern of tourist perceptions. Visitors highly value the park’s natural landscape, shaded environment, and free fruit-picking experiences as its primary attractions. Conversely, sanitation facilities, playground cleanliness, parking management, and inter-institutional coordination are perceived negatively due to limitations in operational maintenance resources. The study further identifies the emergence of a “Tragedy of the Commons” phenomenon, whereby the free-entry policy has gradually shifted the destination’s function from an educational agritourism site to a lowcost recreational space. The findings suggest that sustaining public agritourism destinations requires collaborative governance mechanisms, including Public–Private–Community Partnerships (PPCP), digital interpretation initiatives, the revitalization of environmental education programs, and improved spatial planning for local MSMEs. This study contributes to the sustainable tourism literature by providing empirical evidence on the governance challenges of free-access agritourism destinations in emerging economies. Keywords: Tourist Perception; Destination Management; Public Agritourism; S-O-R Model; Lubuk Pakam Fruit Park